Synthesis, structures, and photocatalytic properties of three new nickel(II) coordination polymers containing bis(benzimidazole) ligands with different coordination architectures. (1st April 2020) - Qu, Yun-Hua; Yang, Ying-Jie; Dong, Gui-Ying
Graphical abstract: Three new nickel(II) CPs based on 1, 4-bis(benzimidazol-1-yl)-2-butylene and dicarboxylic acids coligands were successfully synthesized and characterized. The photocatalytic properties of three CPs under UV irradiation were investigated in detail. Highlights: Three Ni(II) coordination polymers were synthesized and characterized. Carboxylate coligands have important effects on the structural diversity of CPs. Three CPs present excellent water stability. Three CPs show highly photocatalytic activities for degradation of MB under UV irradiation. Three CPs exhibit highly stability and can be recycled five times. Abstract: Three new nickel(II) coordination polymers with the formulas of [Ni(L)(5-HIP)]·H2 On (1 ), [Ni(L)(2, 6-NDC)]n (2 ) and [Ni(L)(OBA)]n (3 ) were synthesized under solvothermal conditions employing 1, 4-bis(benzimidazol-1-yl)-2-butylene (L) and aromatic dicarboxylic acids ligands (5-H2 HIP = 5-hydroxyisophthalic acid; 2, 6-H2 NDC = 2, 6-naphthalenedicarboxylic acid; H2 OBA = 4, 4'-oxybis(benzoic acid)). 1 displays an unusual 3D (3, 6)-connected framework with the Schläfli symbol of 6 3 6 7 .8 3 , 2 features a 3D 3-fold interpenetrated sqc6 network, 3 possesses a 2D 2-fold interpenetrated network with sql topology. 1 3 present highly photodegradation efficiency for methylene blue under UV irradiation.